Psychometric adaptation of the Reynolds Adolescent Depression Scale in Peruvian secondary students in metropolitan Lima - Ugarriza, Nelly (2002)
Percentile norms are presented for the Reynolds Adolescent Depression Scale (RADS). They were obtained from a sample of 1.963 Peruvian secondary students, all men and women, from public and private schools. The alpha coefficients obtained were above .87, showing the internal consistency of the scale. It was found that depression is higher in women and in public schools’students. Factorial analyses were performed: the rotated six factor orthogonal solution (Varimax) was obtained accounting for 45,8 percent of the total variance: Demoralization, anger and sadness, anhedonia, low self-esteem, somaticvegetative and school anxiety.